Resilience, tutorial orientation and perception of competition in college students from a public university - Obregón Alzamora, Norka Inés (2018)
The present research seeks to establish how the relationship between resilience, tutorial orientation and perception of competence in university students of a public university in Metropolitan Lima. To achieve this goal, three measuring instruments were built for data collection: resilience questionnaire, tutorial orientation questionnaire and competence perception questionnaire, fulfilling validity and reliability criteria. Its application allowed to know the levels of resilience that the university student has and how it influences along with the tutorial orientation, in the process of the perception of competences. Finally, the conclusions reached is that students with a higher level of resilience, the greater the perception of competencies; it means, they are associated, while the tutorial orientation and the perception of competence are in an independent relationship, because the first does not apply in the training of the university student.